Stainless steels in ammonia production. (Nickel Institute, 2020)
The purpose of this booklet is to identify the many applications of stainless steels in a typical process for manufacturing anhydrous ammonia.
"Originally, this handbook was published in 1978 by the Committee of Stainless Steel Producers, American Iron and Steel Institute. The Nickel Institute republished the handbook in 2020."
Keywords: Ammonia -- Synthesis.; Stainless steel.; elektronické knihy; electronic books